An Assessment of the World Bank-Assisted FADAMA II Project Towards Sustainable Rural Development in Kaduna State, Nigeria - Yakubu, Umaru Ibrahim; Usman, Ahmed (Kashere Journal of Politics and International Relations, 2024)
The World Bank’s intervention in Nigeria’s rural development has not yielded sustainable improvement in the living conditions of rural dwellers who are predominantly smallholder farmers. Many reasons have been attributed to this failure such as corruption and bad governance. This paper assesses the World Bank-supported FADAMA II project with a focus on sustainable rural development in Kaduna State. Using the dependency theoretical perspective and primary data generated through a survey of 400 farmers, the paper assesses the project’s achievements in three aspects. The first being knowledge uptake on good agricultural practices, the second is access to agricultural inputs and the third is financial viability among project beneficiaries in Kaduna State. The paper argues that the sustainability of the project’s achievements in the state within the three aspects is uncertain. This is largely attributed to the project design which can hardly engender sustainable rural development. Therefore, the paper recommends that the state commits more resources and becomes more effective in its rural development efforts, rather than depend on donor support to develop the rural areas.